Feed supplementation with a mixture of C1 to C12 monoacylglycerides increases chicken resistance to Salmonella Enteritidis infection - Faldynova, Marcela; Volf, Jiri; Karasova, Daniela; Prikrylova, Hana; Sebkova, Alena; Mullerova, Adela; Kucerova, Renata; Skalickova, Sylvie; Rychlik, Ivan (Poultry science, 2025)
Chickens represent one of the most important sources of animal protein for the human population. However, chickens also represent one of the most important reservoirs of Salmonella for humans. Measures to decrease the Salmonella incidence in chickens are therefore continuously sought. In this study, we tested feed supplementation with a mixture of C1 to C12 monoacylglycerides. At 0.7 and 1.5 kg per ton of feed, such supplementation significantly decreased Salmonella counts in the caecum but not in the liver. The chickens were infected on day 4 and the protective effect in the caecum was recorded on day 22 and 23 of life. Supplementation also decreased the inflammatory response of chickens to Salmonella infection determined by avidin, SAA, ExFABP, MMP7, IL1β, IL4I and MRP126 gene expression but did not affect immunoglobulin expression in the caecum. C1 to C12 monoacylglycerides can be used as a feed supplement which, if continuously provided in feed, decrease Salmonella counts in chickens just prior slaughter.
Keywords: potravní doplňky; Diet; Disease Resistance; Animal Feed; kur domácí; Male; Cecum; Poultry Diseases; nemoci drůbeže; Salmonella Infections, Animal; krmivo pro zvířata; Chickens; Animals; Caecum; náhodné rozdělení; Dose-Response Relationship, Drug; dieta; monoglyceridy; zvířata; Random Allocation; mužské pohlaví; odolnost vůči nemocem; salmonelová infekce u zvířat; Monoglycerides; Monoacylglyceride; Chicken; Salmonella enteritidis; vztah mezi dávkou a účinkem léčiva; cékum; Dietary Supplements; Salmonella